When Algorithms Shape Trust: The Capitalist Transformation of Digital Islamic Da’wah in Indonesia - Fadilla, Siti; Isma Indriyani, Putri (Surau Journal of Islamic Studies, 2025)
This study investigates the capitalist transformation of digital Islamic da’wah in Indonesia through the lens of social media algorithms and their role in shaping user trust. Employing a qualitative literature review approach, the research analyzes how algorithmic mechanisms prioritize content circulation based on engagement metrics, thereby influencing the production and reception of religious messages. The findings reveal that digital platforms driven by capitalist imperatives commodify Islamic da’wah, altering its communicative style and potentially compromising its spiritual authenticity. This commodification fosters a competitive digital environment where trust is algorithmically constructed and leveraged for monetization. The study underscores the critical need for digital literacy among Islamic preachers and their audiences to navigate these dynamics responsibly. Limitations include reliance on secondary sources without primary empirical data, highlighting the importance of future multifaceted research to develop ethical and effective digital da’wah strategies in a rapidly evolving media landscape. The research implications advocate for balancing technological adaptation with the preservation of genuine Islamic values against the pressures of digital capitalism.